TQM practices and its association with production workers - Ooi, Keng-Boon; Arumugam, Veeri; Teh, Pei-Lee; Chong, Alain Yee-Loong (EMERALD GROUP PUBLISHING LIMITED, 2008)
Purpose - The purpose of this paper is to investigate the multidimensionality of total quality management (TQM) practices and its relationship with production workers' job satisfaction in the Malaysian electrical and electronics (E&E) industry context.